Thermo-responsive properties of self-healable thermosets based on epoxidized soybean oil - Tercjak, Agnieszka (2024)
In this work, epoxidized soybean oil (ESO) based thermosetting materials cured with citric acid (CA) and modified with low molecular weight 4′-(hexyloxy)-4-biphenyl-carbonitrile (HOBC) nematic liquid crystal were synthesised and characterized. In order to find adequate curing conditions, the non-isothermal differential scanning calorimetry (DSC) was performed and the formation of thermosetting systems was confirmed by Fourier transform infrared spectroscopy (FTIR). As expected, the addition of HOBC nematic liquid crystal affected strongly the curing reaction of ESO/CA mixture. Thus, HOBC liquid crystal phase was partially miscible with ESO for low HOBC content, while its phase separation from ESO/CA matrix was detected for more than 20 wt% HOBC content. Thermal behaviour and thermal stability depend strongly on HOBC content leading, for high HOBC content, to thermosetting systems with nematic-isotropic transition characteristic for HOBC liquid crystal. Optical properties of HOBC-ESO/CA thermosetting systems confirmed the capability of HOBC liquid crystal phase to switch reversibly photoluminescence properties applying temperature. Moreover, an improvement of the thermo-responsive behaviour (shorter switching time and sharper switching temperature range) can be obtained modifying developed system with a small amount of poly(ε-caprolactone-b-lactide) (CLLA) block copolymer. Designed HOBC-ESO/CA thermosetting systems maintained self-healing properties attributed to ESO/CA thermosetting system. Thus, HOBC-ESO/CA thermosetting system modified with CLLA block copolymer was able to reach an interface width reduction of 98% after 2 h of self-healing process at 160 °C. This research work allowed to develop thermosetting systems, which combine self-healing properties of ESO/CA matrix with thermo-responsive properties of HOBC liquid crystal phase. Designed thermosetting materials can broad potential applications of ESO/CA thermosetting system.